Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade